2015
DOI: 10.2460/javma.247.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Detemir insulin for the treatment of diabetes mellitus in dogs

Abstract: Results suggested that SC injection of insulin detemir every 12 hours may be a viable treatment for diabetes mellitus in dogs. Insulin detemir dosages were lower than reported dosages of other insulin types needed to maintain glycemic control, suggesting that insulin detemir should be used with caution, especially in small dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 26 publications
2
20
0
3
Order By: Relevance
“…Though detemir's time action profile was relatively consistent amongst dogs, its duration of about 11 hours action coupled with a significant peak does not allow for once daily administration without a relatively high risk of hypoglycemia. A previous clinical trial using insulin detemir in canine diabetics has highlighted similar concerns even when used every 12 hours (at the dose used in this study), with 6 episodes of clinical hypoglycemia observed in 4 dogs in a 6-month period in one study [21].…”
Section: Endogenous and Exogenous Insulin Measurementsupporting
confidence: 52%
See 3 more Smart Citations
“…Though detemir's time action profile was relatively consistent amongst dogs, its duration of about 11 hours action coupled with a significant peak does not allow for once daily administration without a relatively high risk of hypoglycemia. A previous clinical trial using insulin detemir in canine diabetics has highlighted similar concerns even when used every 12 hours (at the dose used in this study), with 6 episodes of clinical hypoglycemia observed in 4 dogs in a 6-month period in one study [21].…”
Section: Endogenous and Exogenous Insulin Measurementsupporting
confidence: 52%
“…Furthermore, it has been shown that within insulin type and preparation, considerable variation exists. This results in difficulty establishing ideal doses and dosing intervals for each patient [19][20][21][22][23][24][25][26][27]. Specific insulin types are described in more detail in the following chapter.…”
Section: Chapter 2: Treatment Of Diabetes Mellitus In the Canine Patientmentioning
confidence: 99%
See 2 more Smart Citations
“…A glicemia sérica é afetada por diversos fatores, como, por exemplo, variação diurna, exercício, estresse, alimentação e medicação, o que não ocorre com a hemoglobina glicada e a frutosamina (9) , aumentando a margem de confiança para afirmar que o cão está com glicemia elevada e por tempo prolongado (10) . Ambas as substâncias são geradas pela interação com a glicose plasmática (11,12) . Foi possível notar que a correlação mais elevada ocorreu entre a glicose e a hemoglobina glicada, resultado este observado também na comparação das avaliações entre animais sobreviventes e não sobreviventes, pois foram as únicas que mostraram resultados menores no grupo sobrevivente (Tabela 3).…”
Section: Resultsunclassified